PENGARUH KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PT. BANK DANAMON INDONESIA, TBK CABANG SIMPANG PASAR BAWAH - Dianita, Nana (Eko dan Bisnis: Riau Economic and Business Review, 2019)
The purpose of this study was to determine the effect of competence on the performance of employees at PT. Bank Danamon Indonesia, Tbk Cabang Simpang Pasar Bawah. The sample in this study were all employees at PT. Bank Danamon Indonesia, Tbk Cabang Simpang Pasar Bawah totaling 34 people. While the variables studied in this research is the competence and performance. Analysis of data using simple linear regression method using validity, reliability, R2 and t test. The tests are conducted to determine the relationship between the independent variables (independent variables) and dependent variable (dependent variable). Based on research results the effect of competence on the performance of employees with correlation value R = 0,656 which indicates a close relationship between the effect of competence on the performance of employees at PT. Bank Danamon Indonesia, Tbk Cabang Simpang Pasar Bawah. While the R-square at 0,430 which can competence has contributed of 43% to the performance of employees at . Bank Danamon Indonesia, Tbk Cabang Simpang Pasar Bawah. Partially acquired competence variable positive and significant effect on the performance employees at . Bank Danamon Indonesia, Tbk Cabang Simpang Pasar Bawah with simple linear regression equation as follows: Y = 18,342 + 0,627X significantly smaller 0,000 than alpha 0,05. The conclusion of this study that partial hypothesis between variables competence on performance employees is proven and can be accepted as true